Feeding strategies and main expenses in sheep breeding in mountainous area of Tizi-Ouzou, Algeria - Mouhous A.; Chibane F.; Segheir S.; Brabez F.; Kadi S.A. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
With the aim to identify the feeding strategies of sheep breeders in relation with expenses of sheep and the role of pasture in the feeding of the herd, a regular follow-up of 16 sheep farms in mountain area of Tizi-Ouzou (Algeria) was adopted during one year. The first results show that these strategies are related to climate and to period of strong complementation such as the complementation in periods of lambing or fattening in order to sale. For 37% of the farmers, sheep breeding is considered as the main activity of which herd size varies from 7 to 75 heads. The average time spent by animals in pasture is 6 hours/day. The Rangelands and natural grasslands are used throughout the year. The animals receive an average of 54 g/head/day of feed complement. The complement is often wheat bran, concentrates, corn and barley. For this purpose, the feed cost reaches 240 DA1/head/month; this represents 24% of total operating expenses. The use of mountain pasture seems secure sustainability strategies adopted by farmers.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)